The devil is in the details: emerging insights on the relevance of wastewater surveillance for SARS-CoV-2 to public health. (28th December 2021) - Hrudey, Steve E.; Conant, Bernadette
Abstract: The severe health consequences and global spread of the COVID-19 pandemic have necessitated the rapid development of surveillance programs to inform public health responses. Efforts to support surveillance capacity have included an unprecedented global research response into the use of genetic signals of SARS-CoV-2 in wastewater following the initial demonstration of the virus' detectability in wastewater in early 2020. The confirmation of fecal shedding of SARS-CoV-2 from asymptomatic, infected and recovering individuals further supports the potential for wastewater analysis to augment public health conventional surveillance techniques based on clinical testing of symptomatic individuals. We have reviewed possible capabilities projected for wastewater surveillance to support pandemic management, including independent, objective and cost-effective data generation that complements and addresses attendant limitations of clinical surveillance, early detection (i.e., prior to clinical reporting) of infection, estimation of disease prevalence, tracking of trends as possible indicators of success or failure of public health measures (mask mandates, lockdowns, vaccination, etc.), informing and engaging the public about pandemic trends, an application within sewer networks to identify infection hotspots, monitoring for presence or changes in infections from institutions (e.g., long-term care facilities, prisons, educational institutions and vulnerable industrial plants) and tracking of appearance/progression of viral variants of concern. HIGHLIGHTS: Wastewater-based surveillance (WBS) for the pathogen SARS-CoV-2 has experienced phenomenal growth in application across much of the world. Widespread adoption of WBS is relevant and useful where it can provide evidence that can reliably inform public health responses. The potential for WBS to provide early warning of the emergence of COVID-19 infection in relation to clinical testing is attractive but capability depends on specific details of WBS logistics. WBS data offers the advantage of being independent of extraneous factors such as policies governing clinical testing and data can be regarded as objective provided adequate QA/QC programs are provided to ensure validity of genetic signals of SARS-CoV-2 that are measured in wastewater. The potential for WBS to track the appearance and progression of viral variants of concern (VOC) in a sewered population has assumed increasing importance as the emergence of VOCs has proven challenging for managing the COVID-19 pandemic particularly as rapidly rising case counts pose a challenge for clinical testing. Graphical Abstract